Fluoride in Drinking Water and its Correlation with Dental Caries in Northern Rural Areas of Bangladesh (Update Dental College Journal, 2025)
Objective: The aim of this study is to evaluate the prevalence of dental caries and its relationship with fluoride levels in drinking water. Fluoride concentrations were analyzed in six different Upazilas of Naogaon, located in the northern region of Bangladesh.Methods: The study included a total of 120 dental caries patients from these six Upazilas, with 60 males and 60 females. The fluoride concentration in drinking water was evaluated by utilizing the (SPADNS) method. The findings indicated that Sapahar Upazila exhibited the lowest concentration of fluoride in drinking water at 0.118±0.12 mg/L whereas Manda Upazila exhibited the highest mean frequency of fluoride concentration in drinking water, which was recorded as 0.875±0.34 mg/L.Results: It was found that DMFT (Decayed, Missing, Filled teeth) value gradually decreased with increasing water fluoride levels from >6.5 mg/L. Conversely, DMFT increased progressively when water fluoride levels dropped below 1.1 mg/L. Sapahar exhibited a significantly higher incidence of dental caries (94.7%) compared to other Upazilas despite having the lowest fluoride level (0.190±0.06) with the highest DMFT index (7.124±0.62).Conclusion: The study observed that low levels of fluoride in the studied area are a major contributing factor to dental caries, necessitating increased awareness among the population. Additionally, the use of fluoride toothpaste is recommended to address the issue in areas where the fluoride concentration in drinking water falls below 0.5 mg/L.Update Dent. Coll. j: 2025; 15(1): 37-42